Pengembangan LKPD Gerak Harmonik Sederhana Berbasis Hands On dan Minds On Activity untuk Meningkatkan Hasil Belajar Peserta Didik - Rina Ramadhani; Sarah Miriam; Saiyidah Mahtari (Universitas Hamzanwadi, 2020)
Student worksheet based on hands on and minds on activity that designed to improve student learning outcomes is not yet available, especially for simple harmonic movement. The aims of this research are to produce simple harmonic movement’s student worksheet based on hands on and minds on activity that are valid and practice. The model that used for this research is the ADDIE model, within simple harmonic movement’s student worksheet based on hands on and minds on activity as the subject of this research. The data of this research is obtained from validity sheets and assessment sheets of student worksheet legibility by students. Data analysis was performed through the validity tests and the average score of student worksheet legibility by students. This research shows that: (1) the validity of simple harmonic movement’s student worksheet based on hands on and minds on activity is 3,23 that categorized as valid; and (2) the practicality of simple harmonic movement’s student worksheet based on hands on and minds on activity is 72,00% that categorized as practice. It can be concluded that simple harmonic movement’s student worksheet based on hands on and minds on activity can be used in the learning process.DOI: 10.29408/kpj.v4i2.2549